Safety and efficacy of Ofatumumab in chronic lymphocytic leukemia: a systematic review and meta-analysis. Issue 10 (26th November 2017) - Wu, Yougen; Wang, Yang; Gu, Yuting; Xia, Ju; Kong, Xiaoyang; Qian, Qingqing; Hong, Yang
ABSTRACT: Objectives: Increasing numbers of clinical studies have been carried out to investigate the therapeutic effect of Ofatumumab for patients with chronic lymphocytic leukemia (CLL) but no studies have yet reported a pooled estimate of the treatment effect. We performed a meta-analysis of evidence from 13 clinical trials to assess effectiveness and safety of Ofatumumab-based therapy in patients with CLL. Methods: Relevant publications from PubMed, Web of Science, Embase, and ClinicalTrials.gov were searched. The primary efficacy outcomes were progression-free survival (PFS) and overall survival (OS). The second endpoint was the adverse events. Results: The pooled efficacy analysis showed that there were no significant difference in PFS [hazard ratios (HR) = 0.88, 95% confidence interval (CI) = 0.47–1.63, p = 0.677, I 2 = 94.9%] and OS (HR = 0.97, 95% CI = 0.70–1.36, p = 0.878, I 2 = 58.7%) between Ofatumumab-based therapy and non-Ofatumumab therapy. The pooled toxicity analysis showed that Ofatumumab-based therapy was associated with an increased risk of infusion-related reaction but decreased risk of thrombocytopenia and anemia compared with non-Ofatumumab-based therapy. Moreover, infections, and infusion-related reaction occurred more frequently in participants with single Ofatumumab studies. Discussion: Our analysis showed PFS was statistically significantly improved with Ofatumumab-based treatments (including Ofatumumab alone, Ofatumumab plus chemotherapy) for CLL compared with observation or chemotherapy-based regimen groups. Ofatumumab had no statistically significant improvement on the OS of patients with CLL. The Ofatumumab-based therapy could generally decrease the risk of adverse effects except infusion-related reaction and infections.